Preliminary evidence on the safety profile of BNT162b2 (Comirnaty): new insights from data analysis in EudraVigilance and adverse reaction reports from an Italian health facility - Michele Gringeri; Giulia Mosini; Vera Battini; Gianluca Cammarata; Greta Guarnieri; Carla Carnovale; Emilio Clementi; Sonia Radice (Taylor & Francis Group, 2021)
The first vaccine against SARS-CoV-2 made available in Italy has been BNT162b2, the two-dose mRNA-based vaccine developed by Pfizer-BioNTech. The ASST Fatebenefratelli-Sacco hospital is located in one of the areas most affected by the pandemic, and to date over 2000 healthcare professionals have been injected with both vaccine doses. We have collected all spontaneous safety reports in which BNT162b2 was designated as the possible cause. We also have carried out a descriptive analysis of reports submitted in EudraVigilance in the same time-frame and compared our findings with those observed in clinical trials. We have identified several new and unexpected adverse reactions that will be helpful for reviewing the safety profile defined in the Summary of Product Characteristics for this vaccine.